Forward-focused coping predicts better mental health outcomes in mid- to late-life during the COVID-19 pandemic. (4th March 2022) - Jordan, Leslie S.; Woodard, John L.; Pena, Gabriel S.; Arnold-Nedimala, Naomi A.; Won, Junyeon; Callow, Daniel D.; Smith, J. Carson
Abstract: Objectives: Psychosocial stressors associated with the COVID-19 pandemic may increase the risk of depression and anxiety in the general population. Individuals approaching or within older adulthood may be especially vulnerable to these psychosocial stressors and their impact on mental health outcomes. Consequently, there is an urgent need to identify protective factors for older adults. The purpose of the present study was to determine the relative contribution of coping flexibility (CF) and two distinct coping strategies, forward-focused and trauma-focused, on negative affect in persons 50 years of age and older during the COVID-19 pandemic. Method: Data were collected using an online survey, including questions about demographic information, coping, depression, and anxiety. Participants aged 50 and over were included in our analyses of depression ( N = 800) and anxiety ( N = 638). Results: Both higher CF and higher forward-focused coping predicted lower depression and lower anxiety. In contrast, higher trauma-focused coping predicted slightly higher depressive symptoms but was not a significant predictor of anxiety. Conclusion: Our findings suggest that higher forward-focused coping may serve as a protective factor in older adults during the pandemic and, therefore, may be an effective treatment target for mental health interventions.